Estimation of forest Carbon Stocks in Ba Be National Park, Bac Kan province, Vietnam (Forest and Society, 2020)
Climate change and an increase in the greenhouse effect are a matter of global concern. One of reasons for this phenomenon is the increase in greenhouse gases, especially CO2. Therefore, the authors investigated CO2 absorption from forests of 45 plots in Ba Be National Park, characterized by 3 forest states as rich, medium and poor forest, rehabilitated forest after exploitation to estimate carbon sequestration of the forest. In which, the carbon stock of rich forest reaches 273.17 tones/ha, the medium forest is 136.23 tones/ha and the poor forest, rehabilitated forest is 42.06 tones/ha. With a forest growth rate of 1.8% per year, the carbon sequestration in Ba Be National Park for 3 forest states is about 16,499 tones per year. This will contribute to improve environmental quality, reducing greenhouse gas emissions and creating a scientific basis for managers to develop a payment mechanism of forest carbon sequestration services.
Keywords: Forest carbon; carbon sequestration; natural forest; Ba Be National Park